Proteomic characterization and comparison of Malaysian Bungarus candidus and Bungarus fasciatus venoms - Ahmad Rusmili, Muhamad Rusdi; Ting, Tee Yee; Mustafa, Mohd Rais; Hodgson, Wayne C.; Othman, Iekhsan (Elsevier Ltd., 2014)
Kraits (Bungarus spp.) are highly venomous elapids that are only found in Asia. In the current study, 103 and 86 different proteins were identified from Bungarus candidus and Bungarus fasciatus venoms, respectively. These proteins were classified into 18 different venom protein families. Both venoms were found to contain a high percentage of three finger toxins, phospholipase A2 enzymes and Kunitz-type inhibitors. Smaller number of high molecular weight enzymes such as L-amino acid oxidase, hyaluronidases, and acetylcholinesterase were also detected in the venoms. We also detected some unique proteins that were not known to be present in these venoms. The presence of a natriuretic peptide, vespryn, and serine protease families was detected in B. candidus venom. We also detected the presence of subunit A and B of β-bungarotoxin and α-bungarotoxin which had not been previously found in B. fasciatus venom. Understanding the proteome composition of Malaysian krait species will provide useful information on unique toxins and proteins which are present in the venoms. This knowledge will assist in the management of krait envenoming. In addition, these proteins may have potential use as research tools or as drug-design templates.